2023
DOI: 10.1007/s11096-023-01647-0
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal depression screening in community pharmacy: Exploring pharmacists’ roles, training and resource needs using content analysis

Clara Strowel,
Camille Raynes-Greenow,
Lily Pham
et al.

Abstract: Background Perinatal depression (PND) screening is often recommended in primary care settings, which includes the community pharmacy setting. However, there is limited research exploring pharmacists’ perspectives on their roles in screening for perinatal mental illness. Aim This study aimed to explore pharmacists’ views of pharmacists’ roles in PND screening, as well as training and resource needs for PND screening in community pharmacy settings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The TFA defines acceptability as a multifaceted construct, comprising of seven domains (affective attitude, burden, ethicality, intervention coherence, opportunity costs, perceived effectiveness, and self-efficacy, see Table 1 for construct definitions) that can be applied at different timepoints (before, during or after an intervention) to assess the prospective, concurrent, or retrospective acceptability of an intervention. Perinatal research has used the TFA to assess acceptability in a variety of healthcare contexts (e.g., [57][58][59][60][61], including the use of exposure therapy among pregnant women with elevated anxiety (62), and a systematic review on the acceptability of implementing patient reported measures in routine maternity care (63). However, the authors know of no research that has used the TFA to assess the acceptability of suicide-related screening items to perinatal women.…”
Section: Introductionmentioning
confidence: 99%
“…The TFA defines acceptability as a multifaceted construct, comprising of seven domains (affective attitude, burden, ethicality, intervention coherence, opportunity costs, perceived effectiveness, and self-efficacy, see Table 1 for construct definitions) that can be applied at different timepoints (before, during or after an intervention) to assess the prospective, concurrent, or retrospective acceptability of an intervention. Perinatal research has used the TFA to assess acceptability in a variety of healthcare contexts (e.g., [57][58][59][60][61], including the use of exposure therapy among pregnant women with elevated anxiety (62), and a systematic review on the acceptability of implementing patient reported measures in routine maternity care (63). However, the authors know of no research that has used the TFA to assess the acceptability of suicide-related screening items to perinatal women.…”
Section: Introductionmentioning
confidence: 99%